Evaluation of post-market adverse events of lubiprostone: a real-world adverse event analysis from the FAERS database - Qingqing Li; Jijun Zhang; Chuanli Yang; Xiushan Dong; Yan Wang (BMC Gastroenterology)
Abstract Objective Lubiprostone is a selective intestinal chloride channel activator approved for treating chronic idiopathic constipation and constipation-predominant irritable bowel syndrome in adults. However, real-world data on its long-term safety, particularly regarding adverse events necessitating ongoing supplementation, remain limited. Methods Data from the FDA Adverse Event Reporting System (FAERS) database were collected from the second quarter of 2006 to the fourth quarter of 2023. The data was normalized, and various signal quantification techniques such as Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS) were used for analysis. Results A total of 1436 adverse event reports associated with lubiprostone were extracted from the FAERS database. These reports indicated a higher proportion of female patients compared to male patients (65.39% vs. 21.10%). Among those with explicit age data, the largest proportion of patients were 45–65 years old (20.6% of reports), followed by those ≥ 75 (19.9%), 18–45 (14.8%), and 65–75 years (10.1%). Adverse events induced by lubiprostone were observed in 24 System Organ Classes (SOCs), including common gastrointestinal disorders, general disorders, administration site conditions, as well as respiratory, thoracic, and mediastinal disorders, consistent with findings from clinical trials. Applying four algorithms simultaneously, 22 SOCS were detected, revealing a total of 57 positive response items, including 22 related to the digestive system. The most stringent algorithm, empirical Bayesian geometric mean (EBGM), highlighted severe gastrointestinal adverse reactions like gastric fistula (n = 5, ROR = 150.03, PRR = 149.87, IC = 7.21, EBGM = 147.71) and ischemic colitis (n = 19, ROR = 36.78, PRR = 36.63, IC = 5.19, EBGM = 36.51), which were not listed in the drug insert. This suggests the need for heightened vigilance towards these potential adverse reactions during clinical use. Conclusions Our study comprehensively evaluated the safety of lubiprostone in the post-marketing setting. Despite its therapeutic advantages, there is a potential for various systemic adverse effects. In addition to adverse events consistent with information from existing clinical trials and the insert, we discovered several serious localized adverse reactions and previously unreported systemic adverse reactions. These may be potentially associated with lubiprostone, but are not confirmed adverse effects. This will provide valuable evidence for future studies and further prospective clinical trials to confirm these results and elucidate the relationship between them, thus better guiding the clinical practice of lubiprostone.